Biosafe Saccharomyces Cerevisiae Immobilized Nanofibrous Aerogels for Integrated Lead Removal in Human Body. (9th February 2023) - Cao, Shiyi; Wu, Shuangquan; Dong, Xiangyang; Long, Min; Lin, Heng; Liu, Fangtian; Wu, Yang; Zhao, Ze; Chen, Chaoji; Deng, Hongbing
Abstract: Emerging adsorption technology shows great potential for Pb 2+ removal in the human body because of its high adsorption efficiency and easy operation. However, biosafety concerns in the human body limit the development of adsorbents in integrated lead removal for acute poisoning in humans from the gastrointestinal tract and even the blood. In this work, highly bio‐safe and natural saccharomyces cerevisiae cells are immobilized on the interworking natural regenerated cellulose nanofibers network for integrated lead removal in the human body. High intrinsic biosafety of the aerogel is guaranteed due to the biocompatibility of aerogel composition and the absence of cross‐linking substances. Attributing to the porous structure of cellulose nanofibrous scaffolds, saccharomyces cerevisiae cells are protected from shedding, and considerable loading sites for saccharomyces cerevisiae cells are ensured. Simultaneously, abundant functional groups on the saccharomyces cerevisiae cells exhibit superior adsorption ability with a saturated adsorption capacity of lead ions as high as 107 mg g −1 in the aquatic environment. After adsorption, Pb 2+ concentration decreases from 879.70 to 248.53 µg L −1 in the intestinal phase and from 400 to 186.29 µg L −1 (within a safe level) in blood, providing an attractive strategy for detoxification of integrated lead in the human body. Abstract : Porous, biosafe nanofibrous aerogels are fabricated from biomass waste for integrated lead removal in human body. Benefiting from the unique microstructure, high biosafety and abundant active functional groups of the aerogel, the lead ions can be effectively removed from human body, representing a promising solution to lead poisoning.